نظرة المجتمع السوري لمشروعية الأنشطة التأمينية التقليدية والإسلامية في ضوء تعدد الآراء الشرعية (دراسة مقارنة ) - ناصر محمد جودت; العثمان محمد نادر; ديب عماد صديق (Latakia University Journal - Economic and Legal Sciences Series, 2013)
تتناول هذه الدراسة موضوع نظرة المجتمع السوري لمشروعية الأنشطة التأمينية التقليدية والإسلامية،وما يثار حولها من شبهات في ضوء تعدد الآراءالشرعية ، حيث تناولت شبهات القمار والربا وأكل المال الباطل والغرر المفسد للعقود ، حيث تم تصميم استبانة تتضمن الشبهات الأربع ووزعت على /1200/ مواطن سوري من مختلف المحافظات، عاد منها /974/ استبانة صالحة للدراسة بمعدل ( 81,166% ) وتوصلت هذه الدراسة إلى أن المجتمع السوري لا يتفق مع الرأي القائل بعدم مشروعية الأنشطة التأمينية التقليدية، حيث لايوافق على وجود الشبهات الأربعة المذكورة في الأنشطة التأمينية التقليدية ، بينما يوافق على الرأي الذي يعطي المشروعية لأنشطة التأمين الإسلامي حيث يوافق على خلو أنشطته من شبهات القمار والربا وأكل المال الباطل ويرى أن الغرر الموجود فيها غير مفسد للعقد لأنه قائم على التبرع ، والمجتمع السوري يوافق على المزايا الشرعية المنسوبة للتأمين الإسلامي أكثر من درجة موافقته على الانتقادات الشرعية المنسوبة للتأمين التقليدي. وأوصت هذه الدراسة شركات التأمين الإسلامي بضرورة التركيز على الطابع الفني للأنشطة التأمينية في عملية جذب العملاء وعدم الاعتماد على الاعتبارات الشرعية بمفردها لتحقيق عملية الجذب وأن تتوجه إلى المجالات التي يحجم التأمين التقليدي عن التأمين عليها بما يبرز الطابع التعاوني لهذه الشركات This study addresses the issue of Syrian society view for the legitimacy of insurance traditional and Islamic activities, coming under suspicions in the light of the multiplicity of views of legitimacy, addressing suspicions gambling, and usury, eating money falsehood and corrupting deceit in the light of multiplicity of views of decades. A survey has been designed including the four suspicions and distributed to / 1200 / Syrian citizen from various provinces, returned them / 974 / identifying valid to study rate / 81.66% /. This study finds that the Syrian society does not agree with the view of the illegality of traditional insurance activities, where it does not agree on the existence of the four mentioned suspicions in traditional insurance activities while agreeing opinion which gives legitimacy to the activities of Islamic insurance where the activities are free from suspicious gambling, usury and eating falsehood money. It also believes that deceit does corrupt the contract because it is based on donation, and Syrian society agrees on legitimacy advantages attributed to Islamic Insurance more than agreeing to legitimacy criticism attributed to traditional insurance. This study has recommended that the Islamic insurance companies need to focus on thetechnical nature of the insurance activities in the process of attracting customers and not to rely on legitimate considerations alone to achieve the process of attraction and go to areas where the size of traditional insurance including highlights of the collaborative nature of these companies.